Water driven down-the hole well drilling equipment in hard rock - Nordell, Bo; Fjällström, Kent; Öderyd, Lars (Luleå tekniska universitet, Arkitektur och vatten, 1998)
A water driven down-the-hole drilling equipment (Wassara) was developed some years ago at the Kiruna mine, Sweden, which is the largest underground mine in the world. This new drilling technology has been used in their mining production for a few years. It has several advantages to pneumatic drilling methods. This water driven hammer has now for the first time been tested in well drilling (110 mm) in hard rock. The first drilling was done in Örebro for the Swedish telephone company TELIA that is constructing a great number of borehole (direct cooling) systems for their telephone switching stations. The water hammer proved to be considerably more efficient; the drilling speed is about twice as high and the energy consumption is about 1/3, compared to that of the previously used air driven hammers. Another advantage is the possibility to drill several hundred meters in hard rock even in water rich and fractured rock. Experience of the first drilling is summarised. Godkänd; 1998; Bibliografisk uppgift: The Second Stockton International Geothermal Conference March 16 and 17, 1998; 20120608 (ysko)